2016
DOI: 10.1016/j.bios.2016.02.059
|View full text |Cite
|
Sign up to set email alerts
|

An in-situ infection detection sensor coating for urinary catheters

Abstract: We describe a novel infection-responsive coating for urinary catheters that provides a clear visual early warning of Proteus mirabilis infection and subsequent blockage. The crystalline biofilms of P. mirabilis can cause serious complications for patients undergoing long-term bladder catheterisation. Healthy urine is around pH 6, bacterial urease increases urine pH leading to the precipitation of calcium and magnesium deposits from the urine, resulting in dense crystalline biofilms on the catheter surface that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 35 publications
(70 reference statements)
1
59
2
Order By: Relevance
“…Struvite crystals, without proper treatment, can develop into large staghorn calculi (>2500 mm 2 ), with the capacity to fill the entire intrarenal collecting system, irritating the bladder and blocking the flow of urine . Moreover, crystalline biofilms composed of struvite complicate the care of patients undergoing long‐term catheterization due to catheter encrustation and blockage, which impacts approximately 50 % of catheter users . Due to the emergence of antibacterial resistance and reported recurrence rates of 50 %, the standard care involving removal/replacement of catheters and the use of antibiotics is becoming less effective …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Struvite crystals, without proper treatment, can develop into large staghorn calculi (>2500 mm 2 ), with the capacity to fill the entire intrarenal collecting system, irritating the bladder and blocking the flow of urine . Moreover, crystalline biofilms composed of struvite complicate the care of patients undergoing long‐term catheterization due to catheter encrustation and blockage, which impacts approximately 50 % of catheter users . Due to the emergence of antibacterial resistance and reported recurrence rates of 50 %, the standard care involving removal/replacement of catheters and the use of antibiotics is becoming less effective …”
Section: Introductionmentioning
confidence: 94%
“…[17,18] Moreover,c rystallineb iofilms composed of struvitec omplicate the care of patients undergoing long-term catheterization due to catheter encrustationa nd blockage, which impacts approximately 50 %o fc atheter users. [13,[19][20][21] Due to the emergence of antibacterial resistance and reported recurrence rates of 50 %, the standardc are involvingr emoval/replacement of catheters and the use of antibioticsi sb ecoming less effective. [22][23][24][25] Understandingp rocesses of crystallization is crucial for development of improved therapeutics for struvitei nfection stones.…”
Section: Introductionmentioning
confidence: 99%
“…The dual layer is a sandwich structure of poly(vinyl alcohol) (PVA) layer, contains the self‐quenching dye carboxyfluorescein as lower layer and this is capped by an upper layer of the pH responsive polymer poly(methylmethacrylate‐ co ‐methacrylic acid) (Eudragit S100s). The coating was engineered to provide a visual response following a pH trigger, which correlates with an early warning of urinary catheter blockage as a result of P. mirabilis infection ( Figure ) …”
Section: Strategies For Developing Antimicrobial Catheter Surfacementioning
confidence: 99%
“…Schematic illustration of dual‐layered polymeric architecture for pH‐triggered release of 5(6)‐carboxyfluorescein. Reproduced with permission . Copyright 2016, Elsevier.…”
Section: Strategies For Developing Antimicrobial Catheter Surfacementioning
confidence: 99%
“…This sensor relies on the hydrolysis of urea by urease leading to an increase in the pH value of the test solution. Milo et al reported on a new system which could be applied as an early warning of urinary catheter blockage. Urinary catheters were dually coated with a dye‐containing hydrogel as the inner layer and a pH‐responsive polymer as outer coating.…”
Section: Introductionmentioning
confidence: 99%